2016
DOI: 10.1371/journal.pone.0167947
|View full text |Cite
|
Sign up to set email alerts
|

Observations from Mortality Trends at The Children’s Hospital, Accra, 2003-2013

Abstract: ObjectiveFacility-based studies provide an unparalleled opportunity to assess interventions deployed in hospitals to reduce child mortality which is not easily captured in the national data. We examined mortality trends at the Princess Marie Louise Children’s Hospital (PML) and related it to interventions deployed in the hospital and community to reduce child mortality and achieve the Millennium Development Goal 4 (MDG 4).MethodsThe study was a cross-sectional review of data on consecutive patients who died at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
3
3
0
Order By: Relevance
“…The finding in the current study was in line with the mortality trends by Tette et al [14] in Ghana that reported high mortality in males (52.2%) compared to females (47.8%) and similar to other studies in Africa, but it differed from the study in Mali which reported significantly higher case fatality rates among girls. More so, in Zambia, it was found that the mortality pattern was higher in males than females, and the mortality at 24 hours, 48 hours, and 1 week of admission was 93.2%, 88.7, and 29%, respectively [12].…”
supporting
confidence: 90%
“…The finding in the current study was in line with the mortality trends by Tette et al [14] in Ghana that reported high mortality in males (52.2%) compared to females (47.8%) and similar to other studies in Africa, but it differed from the study in Mali which reported significantly higher case fatality rates among girls. More so, in Zambia, it was found that the mortality pattern was higher in males than females, and the mortality at 24 hours, 48 hours, and 1 week of admission was 93.2%, 88.7, and 29%, respectively [12].…”
supporting
confidence: 90%
“…We have shown that mortality rates in AGH ITFC and IPD were in the range of those observed in similar settings, but also consistently high over the study period [3][4][5][6][7]25]. The observed LTFU rates were below those reported in other countries [6,16].…”
Section: Discussionsupporting
confidence: 45%
“…The burden of under-five mortality disproportionately affects low-and middle-income countries, with half of the world's total under-five deaths occurring in sub-Saharan Africa alone [2]. Paediatric inpatient mortality ranges from 3% to 21% across different Sub-Saharan countries and different hospital settings including specialised paediatric care [3][4][5][6][7]. Although Nigeria has seen a consistent reduction in mortality for children under five years of age from 213 per 1000 live births in 1990 to 104 per 1000 live births in 2015, childhood mortality remains high, with the national average reported to be around 120 per 1000 live births in 2017 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, different studies conducted on under-five mortality demonstrated lower mortality rates compared with our study. Observations from the studies conducted in Ghana and Namibia showed under-five mortality of 3.62% and 1.2%, respectively [ 13 , 14 ]. Besides, cohort study on predictors of post neonatal mortality in Western Kenya indicated 4.6% post-neonatal mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%